Warehouse optimization - Tang, Sunny Yew Fai. (2008)
Warehousing is an integral part of every logistics system. It is defined as the part of a firm's logistics system that stores inventory at and between point of origin and point of consumption, and provides information to management on the status, condition, and disposition of items stored. Warehouses traditionally provide storage of inventory during all phases of the logistics process. However, in recent times, warehouses are used more often as a flow-through point rather than a holding point. Warehouses are evolving into distribution centres. This dissertation looks into the warehouse management system of Sunny Logistics Company (SUNLOG), a distribution centre. Studies are conducted into two areas of SUNLOG's warehousing system, namely, the 'Warehouse Storage Optimization' and 'Warehouse Operations Optimization'.